PROFIL TINGKAT KEMATANGAN GONAD IKAN CEMPEDIK (Osteochilus spilurus) DENGAN PEMBERIAN PAKAN JENTIK NYAMUK - Akbar Ridhanie, AL; Ali Iqbal, Ramadhan; Varandry R, Reisza; Kurniawan, Ardiansyah (Jurnal Biogenerasi, 2024)
One of the native fish species found on Bangka and Belitung Islands is the Cempedik Fish, also known as Kepait Fish (Osteochilus spilurus). Due to habitat degradation and overfishing, this species requires domestication efforts. Currently, the achieved domestication level is at the first stage, where the fish can survive in artificial environments. Therefore, research was conducted to enhance gonad maturation in Cempedik Fish by providing natural mosquito larvae feed. This study was carried out from July to September 2024, with fish samples collected from the waters of Tugang Village, West Bangka Regency. At the beginning of the study, the gonad maturity level (GML) of the Cempedik Fish was at stage II, where the gonads begin to partially fill the abdominal cavity. After 45 days of rearing with mosquito larvae feed, the gonad maturity increased to level III. Initially, the fish had a gonadosomatic index (GSI) of 1.28%. This GSI value increased to 1.97% on day 15, 3.7% on day 30, and 5.13% on day 45. These findings indicate a significant increase in gonad weight during the rearing period with natural mosquito larvae feed. The rise in GSI values for Cempedik Fish with natural mosquito larvae feed offers valuable information to support the domestication efforts for this species.